Driver-witness electron beam acceleration in dielectric mm-scale capillaries - Lekomtsev K. V. Konstantin; Aryshev A. S. Aleksandr Sergeevich; Tishchenko A. A. Aleksey Aleksandrovich; Shevelev M. V. Mihail Viktorovich; Lyapin A. Alexey; Boogert S. T. Stewart Takashi; Karataev P. V. Pavel Vladimirovich; Terunuma N. Nobihiro; Urakawa J. Junji (2018, 2018)
Title screen